The Effect of Stress and Working Environment on Employee Performance through Motivation Mediation: A Case Study on International Restaurant in Badung Bali - Kadek Nonik Erawati; Ni Wayan Sitiari; Ni Luh Putu Indiani (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
This study aims to determine the effect of stress and working environment on employee performance through motivation mediation at international restaurants in Badung, Bali. The respondents of this study are laborers at international restaurants in Badung, Bali. The samples of this study are 80 people with the determination of the number of samples which is representative. This study uses partial least square analysis (PLS) with the help of PLS software program. The results of this study indicate that 1) stress gives negative and insignificant effects on employee motivation, 2) stress has negative and significant effect on employee performance, 3) the work environment gives positive and significant effect to motivation, 4) work environment gives negative and insignificant effect on employee performance, 5) motivation gives positive and significant effect on employee performance, 6) motivation is not a mediation between stress and employee performance, 7) motivation is a perfect mediation between work environment and employee performance. The implications of this research are international restaurants in Badung, Bali should pay more attention to the performance of their employees by paying attention to the workload so that the employees do not experience excessive levels of stress. And also pay more attention to the work environment, especially non-physical working environment that is still below the total average, such as: the use of technology.